An exploration of the molecular mechanisms underlying the effects of hyperglycaemia on the autorrhythmicity of cardiac-like stem cells - Menzele, Amanda (Department of Human Biology, 2024)
Introduction Diabetes mellitus with uncontrolled hyperglycaemia is a major risk factor for heart rhythm disturbances. Hyperglycaemia during pregnancy is particularly concerning, as offspring of poorly controlled diabetic mothers are at an increased risk of developing life-long serious cardiovascular complications. Although structural abnormalities such as congenital heart defects and hypertrophic cardiomyopathy are by far the most common sequelae in these infants, it is becoming increasingly apparent that a vulnerability towards malignant dysrhythmias is far more prevalent than generally reported in the literature. Unfortunately, the mechanistic link between hyperglycaemia and impaired foetal cardiac electrophysiology is poorly understood. Using a cardiac developmental cellular model, this study aimed to explore the effects of hyperglycaemia on the autorrhythmicity of mouse embryonic stem cell (mESC)-derived cardiac-like cells.